Human non-contrast T1 values and correlation with histology in diffuse fibrosis. Issue 13 (24th January 2013) - Bull, Sacha; White, Steven K; Piechnik, Stefan K; Flett, Andrew S; Ferreira, Vanessa M; Loudon, Margaret; Francis, Jane M; Karamitsos, Theodoros D; Prendergast, Bernard D; Robson, Matthew D; Neubauer, Stefan; Moon, James C; et al.
Abstract : Background: Aortic stenosis (AS) leads to diffuse fibrosis in the myocardium, which is linked to adverse outcome. Myocardial T1 values change with tissue composition. Objective: To test the hypothesis that our recently developed non-contrast cardiac magnetic resonance (CMR) T1 mapping sequence could identify myocardial fibrosis without contrast agent. Design, setting and patients: A prospective CMR non-contrast T1 mapping study of 109 patients with moderate and severe AS and 33 age- and gender-matched controls. Methods: CMR at 1.5 T, including non-contrast T1 mapping using a shortened modified Look–Locker inversion recovery sequence, was carried out. Biopsy samples for histological assessment of collagen volume fraction (CVF%) were obtained in 19 patients undergoing aortic valve replacement. Results: There was a significant correlation between T1 values and CVF% (r=0.65, p=0.002). Mean T1 values were significantly longer in all groups with severe AS (972±33 ms in severe asymptomatic, 1014±38 ms in severe symptomatic) than in normal controls (944±16 ms) (p<0.05). The strongest associations with T1 values were for aortic valve area (r=−0.40, p=0.001) and left ventricular mass index (LVMI) (r=0.36, p=0.008), and these were the only independent predictors on multivariate analysis. Conclusions: Non-contrast T1 values are increased in patients with severe AS and further increase in symptomatic compared with asymptomatic patients. T1 values lengthened with greater LVMI and correlated with the degree of biopsy-quantified fibrosis. This may provide a useful clinical assessment of diffuse myocardial fibrosis in the future.